Pre-service mathematics teachers' numeracy in Acehnese culture-based minimum competence assessment - Marhami Marhami; Rohantizani Rohantizani; Iryana Muhammad; Samsidar Samsidar; Intan Anggraini (Universitas Hamzanwadi, 2023)
Pre-service mathematics teachers must have good numeracy skills because this ability is needed in all aspects of life, home, work, and society. This study aims to identify the numeracy skills of pre-service teachers on the Acehnese culture-based Minimum Competency Assessment (MCA). A descriptive quantitative method was used in this study with 24 numeracy MCA questions based on Acehnese culture as an instrument. The subject was 158 mathematics education students from three Aceh universities in their fourth and sixth semesters. The data were analyzed quantitatively and categorized based on high, medium, and low levels. The results showed that the overall numeracy ability of pre-service mathematics teachers is 50.06% in the medium category. At the level of knowing and applying, they received 69.38% and 46.62%, which were in the medium category. Meanwhile, they only obtained 39.76% in the low category for reasoning level. It indicated the student’s lack of ability in higher-order thinking. These results are expected to be input for educators to arrange learning that develops the numeracy skills of pre-service teachers.